Determination of The Bioactive Compund and Total Antioxidant Capacity of Apple Species Grown Around Ardahan Region - Z. A. ABACI; E. SEVİNDİK; F. COŞKUN; K. GEZER; A. CELİK; O. KAYGUSUZ; A. ERMİŞ (International Journal of Secondary Metabolite)
Phenolic compounds are seconder metabolytes that have low molecular weight amd they have a high density of presence in frruits and vegetables. Also, they have a antioxidative capacity compared to other bioactive compounds. It was suggested by several researchers that they have beneficial effects that improve human health. It was asserted that Phenolic compounds inhibit cancer cells, helps to decrease blood pressure and antimutagenic activity and it also aids in lowering cardiovascular risks. This study aims to evaluate apple species gathered from Çıldır and Posof which are provinces of Ardahan so that their total antioxidant capacity and bioactive compunds can be determined. This study revealed the total amount of phenolic substances and total sum of anthocyanin in 26 apple species that grows around Ardahan Region. Also, the quantity of dissolvable dry material (SÇKM), pH, titratable acidity, total ascorbic acidity and antioxidant capacity were determined which allowed identification of the nutrition values. The amount of dissolvable dry substance and acidity values were determined by using titremetricmethod based on Cemreoğlu. Identification of total anthocyanin was performed based on Giusti and Wrolstad. Detection of total phenolic substance was found using Folin-Ciocalteu method. Identification of ascorbic acid was done through spectrophotometric method. Antioxidant capacity was determined based on the DPPH sweeper effect. This study led to the finding that 26 different species of apple which are being grown around Ardahan region have high volumes anthocyanin, total phenolic substance and ascorbic acid and that the fruits have elevated antioxidant capabilities. Our study worked on an Uruset which has red iner layers and it was found that the presence of total phenolic substance and antioxidant capacity are high when compared to other species. Both the skin and pulp have high amount of anthocyanin which helps increase the activity of antioxidant.